The relationship between vitamin D status and disease activity in Iraqi systemic lupus erythematosus patients - Zamin Abdulhusssein Al-Sarray; Raghad Hassan Hussein; Ali Hussein Al-Hafidh; Izzat Abdulsatar Al-Rayahi (Journal of the Pakistan Medical Association)
Objective: To find the relationship between vitamin D deficiency and the activity of systemic lupus erythematosusin Iraqi patients.